OPTIMIZATION OF PHENOLIC WASTES TREATMENT IN ARTIFICIAL PRODUCED WATER BY PSEUDOMONAS AERUGINOSA - Syafrizal Syafrizal (Scientific Contributions Oil and Gas, 2016)
The purpose of this research is to obtain the optimum condition of phenol biodegradation in arti􀂿 cially produced water using Pseudomonas aeruginosa. The screening of medium in the highest phenol degradation at 99.85% in medium M5, followed by M1, M4, M3, and M2, at 99.83%, 28.47%, 27.64%, and 0.09%, respectively, during the 24 hours incubation time. Medium M5 and M1 are relatively expensive if applied in the 􀂿 eld, thus optimization of incubation time, temperature, pH, and the adding of oil is needed in the treatment parameters affecting the phenol biodegradation process using an easy and cheap medium, M4. This research resulted in phenol biodegradation percentage at optimum condition for 2 days incubation, pH 7, and temperature 30°C, was 99.98%.The adding of oil at optimum condition: 100 mg/L could degrade phenol waste to 28.01%.